Āryādviśatī - Durvāsas (Mithilā Vidyāpīṭha granthamālā. Prācīnācāryagranthāvalī ;, 1979)
Devotional poem in praise of Lalitā, form of the Hindu deity Durgā, throwing light on esoteric Shaktism; also known as Lalitāstavaratna.